Handheld ED-XRF spectrometers in geochemical investigation: Comparative studies for glacial deposits from Spitsbergen - Kozak, Lidia; Silva Souza, Juliana; Nawrot, Adam; Proch, Jędrzej; Kaźmierski, Marcin; Zawieja, Agnieszka; Niedzielski, Przemysław (Polish Polar Research, 2021)
This study presents the determination of the content of selected metals (Ba, Ca, Fe, Nb, Rb, Sr, Y, Zn, and Zr) in postglacial deposits from two glacial valleys (Ebbadalen and Elsadalen) in the Petunia Bay (southern Spitsbergen). The aim of the research was to experimentally check the usefulness of the handheld energy dispersive X-ray fluorescence technique in the study of samples from the polar zone, before performing the future field tests. Deposit analyses were performed (in parallel) with two handheld X-ray fluorescence spectrometers from different manufacturers, to investigate the accuracy and reliability of the instruments. The statistical analysis of the results indicated that the measurements carried out with two spectrometers were statistically significantly different, which was probably due to the different calibration characteristics used by the manufacturers. However, the analysis of the spatial distribution of element concentrations using Geographic Information System tools showed that the distribution maps of elements concentrations were similar regardless of the spectrometer used in the analyses.